2014
DOI: 10.3389/fnhum.2014.00216
|View full text |Cite
|
Sign up to set email alerts
|

Association of COMT and COMT-DRD2 interaction with creative potential

Abstract: Several lines of evidence suggest that genes involved in dopamine (DA) transmission may contribute to creativity. Among these genes, the catechol-O-methyltransferase gene (COMT) and the dopamine D2 receptor gene (DRD2) are the most promising candidates. Our previous study has revealed evidence for the involvement of DRD2 in creative potential. The present study extended our previous study by systematically exploring the association of COMT with creative potential as well as the interaction between COMT and DRD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 38 publications
(54 reference statements)
1
30
0
1
Order By: Relevance
“…Two trained raters (both were psychology graduate students from Shandong Normal University) were engaged to score all those ideas. The Chinese version of this measure was a widely used noninvasive measure and demonstrated adequate reliability and validity [3, 11, 20, 51, 52]. The inter-rater reliabilities for all the three scores in present study were higher than.…”
Section: Methodsmentioning
confidence: 52%
“…Two trained raters (both were psychology graduate students from Shandong Normal University) were engaged to score all those ideas. The Chinese version of this measure was a widely used noninvasive measure and demonstrated adequate reliability and validity [3, 11, 20, 51, 52]. The inter-rater reliabilities for all the three scores in present study were higher than.…”
Section: Methodsmentioning
confidence: 52%
“…Since the regulation of DA transmission is a complex network involving multiple genes, DRD2 may interact with these genes to affect insight problem solving. Our previous study has shown that DRD2 may interact with COMT to affect divergent thinking flexibility (Zhang et al, 2014a), which is closely related to insight problem solving (Deyoung et al, 2008). And Zabelina et al (2016) recently also reported that divergent thinking and creative achievement could be predicted by the interaction between COMT and DAT1 .…”
Section: Discussionmentioning
confidence: 99%
“…Genetic variants of DRD2 have been repeatedly implicated in insight-related cognitive abilities, such as attention, working memory and cognitive control (e.g., Rodriguez-Jimenez et al, 2006; Zhang et al, 2007; Bertolino et al, 2010; Colzato et al, 2010, 2011; Nymberg et al, 2014; Blasi et al, 2015). More importantly, recent studies have demonstrated that genetic variants of DRD2 are associated with individual differences in divergent thinking ability (Reuter et al, 2006; Runco et al, 2011; Murphy et al, 2013; Zhang et al, 2014a,b; Takeuchi et al, 2015), which is another crucial component of creativity. Based on this evidence, it is reasonable to expect that DRD2 may also play an important role in insight problem solving.…”
Section: Introductionmentioning
confidence: 99%
“…Findings on COMT gene were more controversial. While several SNPs in COMT (rs174697, rs737865, rs5993883, rs4680) were associated with performances in divergent thinking tasks of rCAB (Zhang, Zhang & Zhang, 2014b), other studies failed to find any main effect on either divergent thinking performance in the Abbreviated Torrance Test for Adults (ATTA) or real-life creative achievement measured by the Creative Achievement Questionnaire (CAQ) (Zabelina et al, 2016). Also, individuals carrying the DRD4-7R allele were found to score significantly lower on divergent thinking tasks compared to non-carriers (Mayseless et al, 2013).…”
Section: Introductionmentioning
confidence: 98%